1969
DOI: 10.1063/1.1657425
|View full text |Cite|
|
Sign up to set email alerts
|

Electromigration in Thin Al Films

Abstract: The process of electromigration in thin Al films was studied directly by transmission electron microscopy during passage of current. Due to electromigration, the Al ions migrate along the test strip from cathode to anode, and the actual opening up of holes near the cathode was observed. The rate of hole formation was used to measure an activation energy. For the test strips, a value of 0.7 eV was obtained. In addition, some physical aspects of hole formation, as well as material buildup in the form of hillocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0
3

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(56 citation statements)
references
References 11 publications
1
52
0
3
Order By: Relevance
“…Melmed and Gomer 9 and Barber 10 reported Al whisker growth on a hot tungsten wire and on the wall of a ceramic crucible, respectively, from pure Al vapor. However, there are few reports on the vapor growth of Al whiskers on a flat substrate, although it is possible to achieve the solid phase growth of Al whiskers on flat substrates by either electromigration 11,12 or stress-induced migration. 13,14 In these studies, it is reported that the whiskers are not grown on as-deposited films on a hot substrate.…”
Section: Introductionmentioning
confidence: 98%
“…Melmed and Gomer 9 and Barber 10 reported Al whisker growth on a hot tungsten wire and on the wall of a ceramic crucible, respectively, from pure Al vapor. However, there are few reports on the vapor growth of Al whiskers on a flat substrate, although it is possible to achieve the solid phase growth of Al whiskers on flat substrates by either electromigration 11,12 or stress-induced migration. 13,14 In these studies, it is reported that the whiskers are not grown on as-deposited films on a hot substrate.…”
Section: Introductionmentioning
confidence: 98%
“…The spontaneous growth of metal whiskers from a solid surface is an interesting phenomenon which has been studied for many years [1][2][3][4][5][6], which was reported in many metals or alloys system such as Ag [1], Cd [2,3], Sn [4][5][6][7][8], Zn [9,10], Al [11], In [12], and Pb [13]. Among them, tin whiskers were extensively studied because both the Sn-based plating and solders have been widely used in electronic industry.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 3(b) and 3(c) show two stages of the initial ''forward'' FCE, where a faceted nanogap has begun to form at a point on the left (''upstream'') side of the narrow constriction (movie S3 [15]). At this point we reverse the electron flow of the partially electromigrated lead [13]. Reversing the current causes the faceted nanogap region to refill with gold, demonstrating that the movement of the gold atoms during FCE is in the same direction as the electron flow [ Fig.…”
mentioning
confidence: 99%